(untitled) (Annals of Medical Research, 2021)
Aim: To show midterm results and compare the two methods utilized in pediatric forearm fractures fixation and the risks of radiation. Material and Methods: We conducted retrospective studies of 62 children and adolescent between the age of 6 to 16 years who were exposed to traumatic forearm fractures and treated with methods of fixation mini open reduction and intramedullary K-wire pinning(group 1) and close reduction and intramedullary elastic nailing(group 2). Patient data included age, gender, the mechanisms of injury, fluoroscopic screening time, dose area product (DAP) value, union time, duration of hospitalization, and complications.Results: There was a significant difference in radiation exposure and radiation-related cancer risk in group 2 (P0.001). There was no significant difference between the two groups in the first year of surgery compared to union (p: 0.49), complications and Price CT et al criteria (p: 0,57).Conclusions: If the surgeon’s experience is insufficient, the duration of close reduction and intramedullary nailing operation time and the number of fluoroscopic imaging will increase. This will increase the radiation exposure and the risks associated with radiation for the patient and surgical team. In our opinion, surgeons who do not have enough surgical experience should use open reduction technique to avoid using too much fluoroscopic imaging. Orthopedics surgeons must protect himself, his personnel and the patient from radiation exposure.